World revision of Iteaphila with unbranched radial vein (Diptera: Empidoidea: Iteaphilidae) - Sinclair, Bradley J.; Shamshev, Igor V. (Zootaxa, 2021)
Iteaphila Zetterstedt is redefined to include species with both branched and unbranched radial vein (R4+5) on the basis of a morphological cladistic analysis and parsimony analysis of COI mitochondrial DNA barcode sequences. As a result, Anthepiscopus Becker is hypothesized as a junior synonym of Iteaphila and species of the Iteaphila setosa group are transferred to the new genus, Paraiteaphila gen. nov. The following new combinations are proposed: P. arundela (Shamshev & Sinclair, 2009) comb. nov., P. caucasica (Shamshev & Sinclair, 2009) comb. nov., P. italica (Loew, 1873) comb. nov., P. kubaniensis (Shamshev & Sinclair, 2009) comb. nov., P. merzi (Shamshev & Sinclair, 2009) comb. nov. and P. setosa (Bezzi, 1924) comb. nov. These two genera are assigned to the family Iteaphilidae stat. rev.                Thirty-five species of Iteaphila with unbranched radial vein are revised, including 26 new species: bulbosa species group (I. beringiensis sp. nov., I. bifida sp. nov., I. recta sp. nov., I. tribulosa sp. nov.), macquarti species group (I. bartaki sp. nov., I. falki sp. nov., I. kyrgyzstanensis sp. nov., I. ribesii (Becker, 1891) comb. nov.), nitidula species group (I. longiphallus sp. nov.), nupta species group (I. arnaudi sp. nov., I. bayarea sp. nov., I. brooksi sp. nov., I. dichoptica sp. nov., I. flavipilosa (Coquillett, 1900) comb. nov., I. glabricula sp. nov., I. gracilis sp. nov., I. grandis sp. nov., I. lolo sp. nov., I. longipalpis (Melander, 1928) comb. nov., I. luteitibia sp. nov., I. nupta (Melander, 1928) comb. nov., I. sierrensis sp. nov., I. spinosa sp. nov., I. subnupta sp. nov.), oedalina species group (I. aktruensis sp. nov., I. incus sp. nov., I. miranda sp. nov., I. oedalina (Zetterstedt, 1838) comb. nov., I. polygyna (Melander, 1928) comb. nov., I. recurvata sp. nov., I. sakhalinensis sp. nov., I. zontaki (Nowicki, 1871) comb. nov.), stentor species group (I. parastentor sp. nov., I. stentor (Melander, 1902) comb. nov.) and unplaced to species group (I. caelebs (Becker, 1891) comb. nov.). The following new synonyms are proposed: I. flavicoxa (Melander, 1928) is a junior synonym of I. polygyna (Melander, 1928); I. hirsutus (Melander, 1928) is a junior synonym of I. oedalina (Zettersedt, 1838). Lectotypes are designated for the following species: I. flavipilosa, I. fraternella Zetterstedt, I. nigra Zetterstedt, I. nupta, I. oedalina, I. polygyna and I. ribesii. All species of Iteaphila with unbranched R4+5 are described, key to species presented, male terminalia illustrated, distributions plotted and flowers visited by these species are listed. COI mitochondrial DNA barcode sequences were obtained for 18 identified Nearctic species of Iteaphila with both branched and unbranched R4+5.